2018
DOI: 10.7716/aem.v7i2.656
|View full text |Cite
|
Sign up to set email alerts
|

Tri-band MIMO Antenna for WLAN, WiMAX and Defence System & Radio Astronomy Applications

Abstract: In this paper, an efficacious and impermeable undeviating MIMO consisting of 70 x 50 x 0.4 mm 3 is used for WLAN, defence system & radio astronomy and WiMAX applications. In place of the technique of parasitic elements to abandon the reactive coupling connection between the antennas we have used an alternate technique where a neutralizing line is connected between the two symmetrical radiating elements. In this technique four small slits of small size are etched on to the ground plane to reduce isolation (mutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In literature, different types of design methods have been reported by the researchers for the design of the MIMO antenna [1]- [30] to address the mentioned issues. The design methods include four element closely spaced dual-band radiator [1], planar decoupling structure with higher isolation [2], Hilbert fractal slot [3], F-shaped stubs [4], E-Shaped MIMO Antenna with Matrix of C-Shaped Resonators [5], Multi-band minkowski structure [6], tree shaped ground plane [7], Uniplanar EBG structure [8], complementary split ring resonator [9], folded monopole [10], compact co radiator technique [11], quasi self-complementary structure [12], combination of half planar radiators and ground stub [13], SRR loaded monopole with slotted ground plane [14], parasitic decoupling structure [15], meandering monopole [16], quad elements [17], shared radiator with tapered microstrip feed line [18], CPW-Fed hexagonal ring monopole antenna [19], defected ground structure for enhanced isolation [20], asymmetrical feeding [21], inverted F-antennas [22], inverted L-monopole antenna with interconnected ground plane [23]. Researchers have also investigated printed compact MIMO antennas consisting of open L-shaped slot elements [24], wideband neutralization technique [25], carbon black film technologies [26], and meander line technique [27] to reduce the mutual coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, different types of design methods have been reported by the researchers for the design of the MIMO antenna [1]- [30] to address the mentioned issues. The design methods include four element closely spaced dual-band radiator [1], planar decoupling structure with higher isolation [2], Hilbert fractal slot [3], F-shaped stubs [4], E-Shaped MIMO Antenna with Matrix of C-Shaped Resonators [5], Multi-band minkowski structure [6], tree shaped ground plane [7], Uniplanar EBG structure [8], complementary split ring resonator [9], folded monopole [10], compact co radiator technique [11], quasi self-complementary structure [12], combination of half planar radiators and ground stub [13], SRR loaded monopole with slotted ground plane [14], parasitic decoupling structure [15], meandering monopole [16], quad elements [17], shared radiator with tapered microstrip feed line [18], CPW-Fed hexagonal ring monopole antenna [19], defected ground structure for enhanced isolation [20], asymmetrical feeding [21], inverted F-antennas [22], inverted L-monopole antenna with interconnected ground plane [23]. Researchers have also investigated printed compact MIMO antennas consisting of open L-shaped slot elements [24], wideband neutralization technique [25], carbon black film technologies [26], and meander line technique [27] to reduce the mutual coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In [23], it is observed that the performance evaluation of 5G communication having dual-mode & triple-band MIMO 10-antenna handset array antenna maintains ECC ≤ 0.05. A triband MIMO antenna [24] has a size of 40 × 35 mm 2 for WiMAX, radio astronomy and WLAN applications with reduced isolation (S 12 ) around −52 dB. In [25], a compact multi-band MIMO radiator improved the isolation parameter greatly.…”
Section: Introductionmentioning
confidence: 99%